Pengaruh Kampanye #Tanganmas Oleh BEMP IKOM UNJ Melalui Media Sosial Instagram Terhadap Partisipasi Mahasiswa Ilmu Komunikasi UNJ Angkatan 2020 Dalam Berdonasi - Faliha, Shakilah; Sutjipto, Vera Wijayanti; Safitri, Dini (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research is motivated by the phenomenon of financial difficulties faced by a number of students in continuing higher education. BEMP IKOM UNJ as a student organization took the initiative to conduct the #TanganMas Campaign through Instagram social media to invite students to donate to help colleagues who have difficulty paying tuition fees. The purpose of this study was to determine the effect of the #TanganMas Campaign on the participation of UNJ Communication Science students Class of 2020 in donating. This study uses a quantitative approach with a survey method. The study population was all 82 active students of the UNJ Communication Science study program class of 2020. The sampling technique used saturated sampling, so that all members of the population became the research sample. Data was collected by distributing online questionnaires. The data analysis technique used simple linear regression analysis. The results showed that the #TanganMas Campaign had a significant effect on student participation in donating, with a significance value of 0.000 < 0.05. The magnitude of the influence of the #TanganMas Campaign on Student Participation was 46.5%. It can be concluded that creative digital media-based campaigns carried out by student organizations have proven to be effective in encouraging student participation in social issues in the campus environment.